Al-Akhtā’ al-Imlā’iyah al-Syā’iah ladā Talāmῑż al-Şaf al-Śāmin bi Ma’had Dār al-Ulūm Sipaho - Renni Hasibuan; Linni Zakiyah Siregar (KURAS Institute, 2023)
Actually, the expected objective of this research is to describe, classify, and interpret the forms of Imla' errors in Arabic writing in the eighth grade students of Darul Ulum Islamic Boarding School Sipaho. The research method used in this study is a qualitative approach, based on a descriptive study strategy. Then the researcher used error analysis to analyze the data that had been obtained from students' writing. Then proceed with classifying the data and interpreting it. The research results obtained are that there are four kinds of Imla' errors, where these errors often occur in eighth grade students at Darul Ulum Sipaho boarding school, including: errors in writing line marks and long marks or mad, errors in writing ta' ta'nis and ta' marbuthah, errors in connecting letters, and finally errors in writing letters that are makhorij and are similar and close in nature. Among the four errors, the most common mistakes are in writing line marks and long marks or mad, due to errors This is repeated 37 times in the student's writing.